The Influence of Brand Image and Brand Ambassadors on Consumer Purchase Interest in Scarlett Products - Rani Alika; Nisa Syafitri; Ares Permana (Yayasan Gema Bina Nusantara, 2023)
This research aims to find out whether there is an influence that brand image and brand ambassadors have on consumer purchasing decisions. In this research, researchers used quantitative research methods with causal research. In this research, the target population and sample are women and men who use products from the Scarlett company. The sampling technique used by researchers is purposive random sampling. The sample size was 50 respondents. In this research, the data collection techniques used by researchers were observation and questionnaire techniques. In this research, researchers used the IBM SPSS version 26 program with the aim of analyzing data and calculating statistics on a Windows basis. This research uses multiple regression analyses. The results showed that corporate image, user image, product image, and brand ambassador increased purchasing decisions. With consistent and continuous promotions by brand ambassadors, company can experience a significant increase in sales. Consumers who are interested and confident in the brand will be more likely to buy the company's products. By using brand ambassadors who are well-known and have a wide network, companies can increase the level of public awareness of their brand. Brand ambassadors will promote the brand continuously through social media, events, and shows, thereby creating greater exposure for the brand. People are more interested in and likely to pay more attention to brands promoted by someone they know or admire.